Functional MRI and Attention Deficit Hyperactivity Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The Stroop effect, a measure for selective attention, on behavioral and brain activation of attention deficit hyperactivity disorder (ADHD) children (9 boys, ages 9.8-14.5 years, off or on methylphenidate) and 9 controls was studied using event-related functional magnetic resonance imaging (fMRI) at the Institute of Mental Health, Peking University, Beijing, China, and other centers in China and at Harvard Medical School, Boston, MA, USA.